Investigating how governmentality and governance influence decision making on projects - J. Rodney Turner (Project Leadership and Society (PLAS), 2020)
The literature on project governance suggests an association between good governance and project success. However, the mechanism is not known. It is suggested governance and governmentality influence six psychological constructs, and through them, decision making, and project performance. The six constructs are culture, decision architecture, naturalistic decision making, group working, identity, and social representation. We review six case studies to explore the link between governmentality and governance and the six constructs, and their influence on decision making and project performance. Secondary data were used, using six previously published case studies. We find the six constructs influence decision making and project performance. Thus, we confirm earlier research, to suggest that good governance does often lead to improved project performance and the link is via decision making. Governance creates an environment in which good decisions can be made on projects and assigns competent people to leadership positions.
Keywords: 650; Governance; Decision making; Culture; Choice architecture; Identity; Social representation